Reasons Why Women Choose Home Birth - Mary Angelie P. Andrino; Iris Hope H. Balasoto; Mhelsie Kathrine Zhandee G. Bono; Kathereen R. Canindo; John Laurence G. Casa; Ryan Michael F. Oducado (Asia Pacific Journal of Multidisciplinary Research, 2016)
Maternal deaths in the Philippines remain high. These deaths are mostly due to the large proportion of home births, complications of pregnancy and delivery, and lack of access to facilities and competently trained staff. Utilizing a descriptive, one-shot survey design, the study aimed to determine the reasons why women in a municipality in Iloilo prefer home birth. The respondents were interviewed using a validated questionnaire. Descriptive statistics were used to analyze and interpret the findings. The study revealed that the proportion of home births progressively declined from 2012 to 2014. Birth being imminent or inevitable is the number one reason that supports home birth. Autonomy, safety, affordability, readily available birthing equipment and supplies, accessibility of birth attendant, remote access by going to the birthing center, lack of transportation, and bad weather conditions also led women to give birth at home. Women from the rural areas of the municipality utilized available resources in the community which prompted the predominance of home deliveries assisted by traditional birth attendants (TBAs) and even midwives, who were readily available nearby. This study recommends continuous improvement in existing maternal health interventions and strategies through engagement of women in policy planning, improvement of health service delivery, infrastructural enhancement, better care practices and continuous health education.
Keywords: 330; home birth; home delivery; maternal health; maternal deaths; Philippines